Beneath the lion's gaze : a novel - Mengiste, Maaza (London : Vintage Books, 2010)
An epic tale of a father and two sons, of betrayals and loyalties, o f a family unraveling in the wake of Ethiopia<U+2019>s revolution.
Includes bibliographical references (p. [307]-308).
Keywords: Physicians -- Fiction; Fathers and sons -- Fiction; Families -- Ethiopia -- Fiction; Ethiopia -- History -- Revolution, 1974 -- Fiction; Addis Ababa (Ethiopia) -- Fiction